2006
DOI: 10.1242/jeb.02135
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of foraging dives and lunge-feeding in fin whales

Abstract: SUMMARY Fin whales are among the largest predators on earth, yet little is known about their foraging behavior at depth. These whales obtain their prey by lunge-feeding, an extraordinary biomechanical event where large amounts of water and prey are engulfed and filtered. This process entails a high energetic cost that effectively decreases dive duration and increases post-dive recovery time. To examine the body mechanics of fin whales during foraging dives we attached high-resolution digital tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
356
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 253 publications
(390 citation statements)
references
References 74 publications
22
356
2
Order By: Relevance
“…Although there are many possible explanations for this pattern (Friedlaender et al 2009), we propose an additional hypothesis which suggests that this type of vertical resource partitioning is because of the scaling of lunge-feeding energetics. However, other tag studies have shown the opposite pattern with respect to body size, where humpback whales foraged at a much shallower depth than fin whales (Goldbogen et al 2006(Goldbogen et al , 2008, albeit at different locations. Again, it is clear that more studies are needed to fully understand the effects of lunge-feeding energetics on diving behaviour.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Although there are many possible explanations for this pattern (Friedlaender et al 2009), we propose an additional hypothesis which suggests that this type of vertical resource partitioning is because of the scaling of lunge-feeding energetics. However, other tag studies have shown the opposite pattern with respect to body size, where humpback whales foraged at a much shallower depth than fin whales (Goldbogen et al 2006(Goldbogen et al , 2008, albeit at different locations. Again, it is clear that more studies are needed to fully understand the effects of lunge-feeding energetics on diving behaviour.…”
Section: Resultsmentioning
confidence: 85%
“…The general isometric scaling of propulsion and control surfaces suggests that manoeuvrability and unsteady locomotor performance, such as the ability to accelerate the body during a lunge (Goldbogen et al 2006), will decrease with body size (Webb & Debuffrenil 1990;Domenici 2001). This phenomenon occurs because body mass increases with body size much more rapidly than fluke area or flipper area, both of which are proportional to lift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the bottom phase of U-dives, bowhead whales regularly swim with pitch angles close to zero, rendering the speed estimate unreliable at these times. Therefore, following previous studies (Fletcher et al 1996;Burgess et al 1998;Goldbogen et al 2006;Aguilar Soto et al 2008), we used the lowfrequency flow noise recorded by the tag as an alternative proxy for speed. For each tag placement, we computed the flow noise (noise power at 500 Hz band-pass filtered with a 2-pole Butterworth filter) during descents in 5 s bins along with the mean speed, in that bin derived from the mean vertical speed multiplied by the arcsine of the mean pitch angle over the same interval.…”
Section: Methodsmentioning
confidence: 99%
“…We are, therefore, unable to pinpoint a direct functional consequence of digit loss alone, but the absence of a digit in tandem with a reposition of the digits, may have led to the disparate flipper shapes in mysticete taxa. The narrow and elongate flippers of balaenopterids are probably associated with swimming at high speeds needed for lunge feeding (Goldbogen et al, 2006), whereas the more broad flippers of eschrichtiids and balaenids offer a greater surface area and may aid in low speed turns in shallow lagoons (Benke, 1993). Institution and specimen USNM 500837, 500836, 500838, 500842, 500852, 504350, 504760, 550043, 550357, 500841, 500848, 504317, 504385, 504859, 550063, 550443, 550495, 571014, 571345, 571363, 571256 550179, 550180, 550217, 55020, 550837, 550368, 504461, 504468, 504469, 504498, 550182, 550218, 55021, 504462, 504494, 504499 Tursiops truncatus MMSC 94018, 941016, 571175, 571254, 571265, 571344, 571370, 571713, 571393, 571119, 571149,571096, 571065, 571019, 571133, 571150, 571204,571259, 571269, 571351, 571371, 571121, 571118,571109, 571094, 571127, 571128, 571134, 571152,941016, 571253, 571317, 571364, 571372, 571414,571136, 571093, 571101, 571077, 571030, 571153, 571147, 571154, 571173, 571161, 571167, 571172,571195, 504123, 504121, 484931, NZP-X3080, 504310, 504501, 504881, 550313, 550440, 571162,571177, 571193, 571199, 504122, 500857, 504273,504418, 504541, 550109, 550363, 504295, 504500,504836, 550309 …”
Section: Possible Functional Interpretationsmentioning
confidence: 99%